Antibacterial activity test of Simargaolgaol (Aglaonema modestum Schott ex Engl) leaves extract against Escherichia coli and Salmonella typhi bacteria - Tiurma Solomasi Zega; Putri Mandaoni Pakpahan; Rahmayani Siregar; Givinda Sitompul; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2021)
The Simargaolgaol (Aglaonema modestum Schott ex Engl) plant is a plant that grows wild in Barus District, Central Tapanuli, North Sumatra which is used by the community as a medicinal plant. This study aims to determine the antibacterial activity of n-hexane, ethyl acetate and ethanol extracts from Simargaolgaol leaves against Escherichia coli and Salmonella typhi bacteria. The antibacterial activity test of Simargaolgaol leaves was carried out using the disc diffusion method. The results of antibacterial activity showed that the highest inhibitory power of Simargaolgaol leaf extract was ethanol extract (polar), ethyl acetate extract (semi polar) and n-hexane extract (non polar). The inhibitory power of ethanol extract, ethyl acetate, and n-hexane against Escherichia coli bacteria was 13.1 mm (strong); 9.7 mm (medium); 8.0 mm (medium) and for Salmonella typhi bacteria respectively 11.2 mm (strong); 10.7 mm (strong) and 9.3 mm (medium). With the concentration of the extract in the diameter is 10%. Based on this, it can be concluded that Simargaolgaol leaf extract has potential as an antibacterial.Keywords: Aglaonema modestum Schott ex Engl, Antibacterial activity, Escherichia coli, Salmonella typhi